PENERAPAN METODE ASOSSIATION RULE MINING (ARM) UNTUK MEMPREDIKSI JUMLAH STOK PRODUK PADA SWALAYAN FADHILLAH BENGKULU - Irfan Wendiyansa; Liza Yulianti; Ila Yati Beti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Management of product sales data at Supermarket Fadhillah Bengkulu is still done manually. There is no system that helps predict the amount of product stock and the problem that is often faced is the scarcity of supply of products that are in demand at Supermarket Fadhilla. For decision making in determining the amount of product inventory that can be adjusted to market demand, Fadhilla Supermarkets does not yet use a system and is still calculating manually. Therefore, this research was carried out with the aim of implementing the Association Rule Mining (ARM) method in grouping sales data at the Fadhilla Supermarket. So you can easily determine and classify high product sales. The system implementation uses the PHP programming language and MySQL database and the method used in this research is the waterfall method. After carrying out the Association Rule Mining (ARM) process at the Fadhilla Supermarket with data testing, the results obtained were the highest level of product sales at the Fadhilla Supermarket, Bengkulu. This can be used as a reference by Supermarket Fadhilla for product supplies for the following month. Based on the results of calculations on sales transaction data using the Association Rule Mining (ARM) method with a minimum support of 50% and a minimum Confidance of 75%, the association value of the Association Rule Mining (ARM) method is 93.75%. Keywords: data mining, asossiation rule mining (ARM), swalayan fadhilla Abstrak: Pengelolaan data penjualan produk di Swalayan Fadhillah Bengkulu masih dilakukan secara manual. Belum terdapatnya sistem yang membantu dalam memprediksi jumlah stok produk dan permasalahan yang sering dihadapi adalah kelangkaan pasokan produk yang laris di Swalayan Fadhilla. Untuk pengambilan keputusan dalam menentukan jumlah persediaan produk yang dapat disesuaikan dengan permintaan pasar Swalayan Fadhilla belum menggunakan sistem dan masih dihitung secara manual. Oleh karena dilakukan penelitian ini dengan tujuan untuk mengimplementasikan metode Asossiation Rule Mining (ARM) dalam pengelompokan data penjualan pada Swalayan Fadhilla. Sehingga dengan mudah dapat menentukan dan mengklasifikasikan penjualan produk yang tinggi. Implementasi sistem menggunakan bahasa pemrograman PHP dan Database MySQL dan metode yang digunakan dalam penelitian ini adalah metode waterfall. Setelah dilakukan proses Asossiation Rule Mining (ARM) pada Swalayan Fadhilla dengan uji data maka didapatkan hasil tingkat penjualan produk tertinggi di Swalayan Fadhilla Bengkulu. Hal ini dapat dijadikan acuan oleh Swalayan Fadhilla untuk persediaan produk bulan berikutnya. Berdasarkan hasil perhitungan terhadap data transaksi penjualan menggunakan metode Asosiation Rule Mining (ARM) dengan minimal support 50% dan minimum Confidance 75% maka nilai asosiasi metode Asosiation Rule Mining (ARM) sebesar 93,75%. Kata kunci: data mining, asossiation rule mining (ARM), swalayan fadhilla